THE IMPACT OF TASK-BASED LEARNING ON SPEAKING FLUENCY OF B1 LEARNERS IN UZBEK UNERSITIES (Ustozlar uchun, 2025)
This article explores the impact of Task-Based Language Teaching (TBLT) on the speaking fluency of B1-level English learners in Uzbek universities. The author analyzes the role of TBLT within communicative language teaching, examining how different types of tasks influence learners’ language skills—particularly their oral fluency. Drawing on Paul Nation’s 4/3/2 technique, the concept of fluency is discussed in depth. The article also addresses the importance of task sequencing and highlights the relevance of cognitive approaches in designing effective language syllabi. Through theoretical foundations, prior research, and methodological insights, the study supports the effectiveness of TBLT in enhancing learners’ communicative competence.